Experimental and Numerical Investigation of Sound Absorption Characteristics of Rebonded Polyurethane Foam - Mitrevska, Milica Jovanoska; Mickovski, Viktor; Samardzioska, Todorka; Iannace, Gino (MDPI AG, 2022)
Polyurethane foam (PUF) is an exceptionally adaptable product that has a variety of applications—it can be found almost everywhere. Due to such high utilization, the amount of polyurethane foam waste generated each year is growing over time. Rebonding polyurethane foam waste is a suitable way to progress towards a circular economy. In this paper, the prospect of using rebonded polyurethane foam (RPUF) in noise control applications is examined. An experimental study was carried out on RPUFs with various thicknesses and densities. The sound absorption coefficients at normal incidence and air resistivity were measured. The five-parameter Johnson-Champoux-Allard (JCA) model was adopted for the simulation of the porous layer. The remaining unknown parameters of the JCA model were estimated by inverse acoustic characterization based on fitting the transfer matrix method (TMM) model of an unbounded porous layer with rigid backing to the experimentally obtained sound absorption coefficients. Furthermore, sound absorption coefficients were calculated for a wide range of sample thicknesses, as well as for different air gap thicknesses between the wall and the porous layer. For some of the considered RPUFs, a sound absorption coefficient above 0.8 was achieved over a wide frequency range.